Birds of a feather flock together: Functionally similar vertebrates positively co‐occur in Guianan forests. Issue 3 (18th March 2019) - Denis, Thomas; Richard‐Hansen, Cécile; Brunaux, Olivier; Guitet, Stéphane; Hérault, Bruno
Abstract: Medium‐ and large‐sized vertebrates play a key role in shaping overall forest functioning. Despite this, vertebrate interactions, from competition to mutualism, remain poorly studied, even though these interactions should be taken into account in our conservation and management strategies. Thus, we tackled the question of vertebrate co‐occurrence in tropical rainforests: Are (negative or positive) co‐occurrences dependent on forest structure and composition? and Are these co‐occurrences linked to functional species similarity? We recorded the occurrence of 21 medium‐ and large‐sized vertebrates in 19 French Guianan locations in which a large set of forest structure and composition descriptors were collected. We used a probabilistic model to look for co‐occurrences at different spatial scales, and species pairwise co‐occurrences were then compared to those generated solely on the basis of forest structure and composition. We then quantified the co‐occurrence strength between pairwise species dyads and determined whether they relied on species functional similarity, controlling for the environmental effects. We found that positive co‐occurrences vastly outnumbered negative co‐occurrences, were only partly shaped by the local environment, and were closely linked to species functional similarity. Thus, groups of species sharing similar functional traits are more prone to co‐occur, highlighting the key role of functional redundancy in structuring species assemblages. We discuss how positive interactions could generate the predominance of positive co‐occurrences in oligotrophic terra firme (unflooded) forests when resources are scarce and dispersed in dry season. Finally, we identified functional groups based on co‐occurrence strength and suggested that frugivory/granivory and body size are of primary importance in species interactions in Neotropical vertebrate communities.